Study on Eliminating Delay and Noise in On-Site Audio Center of Anchor Technology - Seung-Won Lee; Soon-Chul Kwon; Seung-Hyun Lee (IEEE Access, 2023)
Audio over IP (AoIP)-based audio transmission technology, which has recently been introduced into the audio market, has led to the development of conventional audio technology. Among the AoIP-based technologies, the audio networks and control hierarchy over peer-to-peer (Anchor) system technology converts audio signals into digital signals and enables real-time transmission and reception without audio loss to a desired location through Internet protocol (IP). In addition, on the receiving side, it allows selecting and mixing multiple transmission signals (audio sources) and controlling transmission and reception signals. The Anchor system replaces the conventional audio mixer and creates a novel paradigm in audio system configuration as it can control transmission and reception signals at a desired location with broadband. However, a delay occurs intermittently or noise is issued at the receiving side of On-site audio center (OAC), a device that transmits and receives audio data. In this study, causes for delay and noise have been analyzed and eliminated through data packet processing in a receiving OAC according to Anchor technology. As a result of the cause analysis, it has been confirmed that there is a data loss due to delay in audio data processing in an audio codec buffer of the receiving OAC. This problem has been solved by eliminating the delay and noise through a controlling algorithm for handling an audio data play speed. As a result of the study, it has been confirmed that high-quality clear audio is played for a long time without delay and noise. It is expected that Anchor technology will be established as a standard for industrial audio system facilities using AoIP technology in the future.